Pengaruh Ling Tien Kung Terhadap Tekanan Darah Lansia Penderita Hipertensi di Desa Cemani - Da Conceição Mendes, Nilda; Firdaus, Insanul; Ermawati, Muzaroah (Pustaka Galeri Mandiri, 2025)
Hypertension is one of the most common degenerative diseases experienced by the elderly. If not properly managed or controlled, it can lead to various complications. Ling Tien Kung exercise is a complementary therapy believed to help reduce blood pressure through simple movements that stimulate blood circulation and the body's energy balance. This study aims to determine the effect of Ling Tien Kung exercise on blood pressure in elderly individuals with hypertension in Cemani Village. This study employed a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 34 elderly individuals with hypertension, selected using purposive sampling. Blood pressure was measured before and after the intervention of Ling Tien Kung exercise, which was performed regularly twice a week for one month. The data were analyzed using the Wilcoxon Signed Rank Test. The results showed that the average systolic and diastolic blood pressure before the Ling Tien Kung exercise was 157.88 mmHg and 94.29 mmHg, respectively, while after the intervention it decreased to 125.74 mmHg and 80.44 mmHg. There was a significant reduction in both systolic and diastolic blood pressure following the Ling Tien Kung exercise. Regular implementation of Ling Tien Kung exercise is effective in lowering blood pressure among elderly individuals with hypertension. Statistical analysis showed a significance value of 0.000 (p < 0.05).